(untitled) (The Research of Medical Science Review, 2025)
Globally, non-alcoholic fatty liver disease (NAFLD) is becoming the most common chronic liver disease. NAFLD is thought to be the hepatic marker of metabolic syndrome, which is frequently linked to metabolic risk factors such diabetes, obesity, hypertension, and hyperlipidemia. The medicinal properties of Astragalus root powder, which is made from the Astragalus plant, are widely recognized. For thousands of years, traditional Chinese medicine has utilized it to boost vitality, fortify the immune system, and enhance general health. Astragalus root powder is high in antioxidants and anti-inflammatory substances, and it is thought to protect against a variety of ailments, improve heart health, and promote healthy ageing. It may also help manage illnesses such as diabetes by balancing blood sugar levels and improving the body's natural defense mechanism. This study aims to assess the chemical, phytochemical, and mineral profiles of Astragalus root powder, as well as its hepatoprotective capabilities. The findings revealed that the raw material was significant in all aspects of its initial analysis for future use in the study. Significant results were obtained from the antioxidant profile, which comprised ferric reducing antioxidant power (FRAP), 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, total flavonoid content (TFC), and total phenolic content (TPC). Measurements of aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatinine, and bilirubin levels were then used to assess the hepatoprotective effect in the experimental groups G1 and G2, which were given dosages of 3g and 6g/day, respectively, and the control group G0, which was not receiving any treatment. The effects of Astragalus root powder on liver enzymes and associated markers were studied before and after two months. The findings revealed that a 6g/day intake of Astragalus root powder for 60 days has highly significant hepatoprotective effects against non-alcoholic fatty liver disease (NAFLD) without any adverse effects.